An intercept study of footbridge users and non-users in Malaysia - Hasan, R. (Elsevier Ltd, 2020)
Road safety of vulnerable road users in low- and middle-income countries (LMICs) is a major concern. Footbridges or overpasses are pieces of infrastructure designed to allow pedestrians to cross safely. Although there is tension over whether footbridges are the most inclusive and sustainable way to support safe road crossing for vulnerable road users, footbridges are still a predominant piece of infrastructure in LMICs. Therefore, research aimed at optimising the use of footbridges could have an impact on the safety of vulnerable road users. The objective of the present study is to understand the motivational factors influencing pedestrian crossing decisions to use a footbridge in Malaysia. Additionally, the present study investigates the effectiveness of some proposed interventions to change the crossing behaviour of footbridge non-users. An intercept study was conducted in five major cities in Malaysia. Pedestrians answered questions regarding their perceptions about footbridges and previous walking experiences. The analysis was divided into two parts: Firstly, a decision tree analysis was conducted to study the relationship between the observed decision to use or not a footbridge and pedestriansâ perceptions about footbridges and experiences. Secondly, a decision tree analysis was used to identify the effectiveness of proposed countermeasures in increasing the footbridge usage among non-users. The findings showed that the footbridge height and the frequency of using it were associated with a decrease in the likelihood of utilising this structure. Being in a hurry was highly associated with crossing at the street level. In addition, footbridge non-users might change their behaviour if escalators or fences are provided as interventions. The results indicated that safety messages delivered through posters to alert footbridge non-users have the potential to sustain safe mobility. A user-centred approach is necessary to increase the usability of footbridges in LMICs. Â© 2020 Elsevier Ltd